Gestão e planejamento regional : o papel do Colegiado de Gestão Regional (CGR) no processo de regionalização da saúde em Mato Grosso - Pedrotti, Priscila Ono (2013)
The Brazilian Constitution of 1988 created the National Health System (SUS), adopting decentralization and regionalization as strategies to consolidate this system. Since then, many initiatives have been implemented, especially the Health Pact, which established the Regional Management Boards (CGR), space for negotiation and agreement, aimed at regional management. This paper seeks to analyze the role of CGR within the process of regionalization in Mato Grosso. Method: qualitative research, consisting of the exploration of 16 CRG’s already created in state, through the usage of self-administered questionnaires and the study of two different cases – chosen through a polarity criteria – after the analysis of all the data retrieved from said questionnaire. The period of analysis referred to the years 2006 to 2012. The investigation was mainly focused on the conformation of the CGR, its operation, organization and relations – also considering management and planning, seeking to understand how this practice works at the regional level. Results: The early incentive given to the regionalization of health in Mato Grosso strengthened regional bodies (CIB Regional and CGR), having the institutionalization been materialized mainly in regard to its regulatory and normative components. Advances were also made in governance, since under the CGR, interests of individuals, governments and organizations were contemplated and established. However, from the self-administered questionnaire, the analysis of database and through case studies, the limitations of state management coordination and induction process of regionalization of health were highlighted, proving that it affects and compromises the NHS management on the analyzed state.